The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1038/s41598-021-82217-0
|View full text |Cite
|
Sign up to set email alerts
|

Value of Patlak Ki images from 18F-FDG-PET/CT for evaluation of the relationships between disease activity and clinical events in cardiac sarcoidosis

Abstract: The association between 18F-fluorodeoxyglucose (18F-FDG) myocardial uptake and clinical presentations in cardiac sarcoidosis (CS) has not yet been clarified. The Patlak slope, Ki, which represents the rate of 18F-FDG uptake is a quantitative index of 18F-FDG metabolism. This study aims to investigate the usefulness of standardized uptake value (SUV) and Patlak Ki images (Ki images) extracted from dynamic 18F-FDG-PET/CT for evaluating the risk of clinical events (CEs) in CS. The SUV and Ki myocardial images wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…There was good correlation between tumour SUV mean and K i indicating that the tumour [ 18 F]FDG concentration was dominated by irreversible uptake in the 20-60 min period used for Patlak analysis [15]. Given the increases in SUV mean that occurred over time we hypothesised that SUV mean measured at earlier times would underestimate K i but this was not the case.…”
Section: Discussionmentioning
confidence: 98%
“…There was good correlation between tumour SUV mean and K i indicating that the tumour [ 18 F]FDG concentration was dominated by irreversible uptake in the 20-60 min period used for Patlak analysis [15]. Given the increases in SUV mean that occurred over time we hypothesised that SUV mean measured at earlier times would underestimate K i but this was not the case.…”
Section: Discussionmentioning
confidence: 98%
“…In a previous study [ 15 ], the usefulness of Patlak Ki images extracted from dynamic 18 F-FDG-PET/CT scan for evaluating the risk of clinical events in CS was examined. The previous study enrolled 21 patients with CS who underwent 30 18 F-FDG-PET/CT scan, which included pretreatment, undertreatment, and follow-up scans, between April 2019 and January 2020.…”
Section: Methodsmentioning
confidence: 99%
“…24 A recent study by Nakajo et al first demonstrated an association of higher K i constants with higher event adverse cardiac event rates in 21 patients with known cardiac sarcoidosis. 25 Overall, parametric imaging offers an opportunity to increase specificity of FDG-PET for CS.…”
Section: Limitations Of Fdg-pet Imaging For Cs Cardiac Metabolic Plasticitymentioning
confidence: 99%